Estimation of protective levels of anti-O-specific lipopolysaccharide immunoglobulin G antibody against experimental Escherichia coli infection. - Schiff, D E (1993)
Serum obtained after immunization with an O18 polysaccharide-toxin A conjugate vaccine was evaluated for the estimation of protective levels of anti-O-specific lipopolysaccharide (LPS) immunoglobulin G (IgG) antibody against bacteremia and death caused by a homologous serotype of Escherichia coli K1 strains. Passive transfer of rabbit serum conferred significant protection from a lethal E. coli infection in a neonatal rat model. The overall incidence of bacteremia and mortality was 4% in rat pups receiving undiluted postvaccination serum, while that in control animals was 100% (P < 0.001). The overall incidences of bacteremia were 5 and 72% for animals with serum anti-O18 LPS IgG concentrations of > 1.0 and < 1.0 microgram/ml, respectively, while the overall incidences of mortality for animals with serum anti-O18 LPS IgG levels of > 1.0 and < 1.0 microgram/ml were 0 and 72%, respectively (P < 0.001). Protection against E. coli infection was also demonstrated with human anti-O18 polysaccharide IgG. None of the animals with human anti-O18 LPS IgG levels of > 1 microgram/ml had bacteremia after bacterial challenge, whereas all animals with bacteremia at 18 h had levels of < 1 microgram/ml. These findings suggest that serum anti-O18 LPS IgG concentrations of > 1.0 microgram/ml may provide protection against bacteremia and death caused by a homologous E. coli K1 infection.